Application of probabilistic analysis in finite element modelling of two dimensional truss - Hasif, Rosazanam (2011)
Finite element analysis (PEA) has become common place in recent years, and is now the basis of a multibillion dollar per year industry. Numerical solutions to even very complicated stress problems can now be obtained routinely using FEA, and the method is so important. This study is about modeling of Two dimensional truss structure using software Ansys 12.0 (APDL) and determines the maximum deflection, maximum stress and maximum strain when the load is applied to the model. Ansys is software based on the finite element analysis (FEA) widely used in the computer-aided engineering (CAE) field. Four random inputs will be used in this study which is Young Modulus (E), Poison Ratio, Radius (R) and Fy loads. The random output will be the graph maximum of deflection, stress and strain. All of the output values should be passing the eight equations of statistics to make sure the values are valid. This study is going to be basic guidelines on how to implement the civil engineering element using Ansys software.